Shorter table ATA evaluation of elementary functions in single precision - Bria, Oscar Norberto
In this paper a slightly modification is proposed to the original Wong and Goto’s ATA method for the computation of elementary functions in IEEE 754 single precision. The identification of a trade-off leads to the proposition of a different chunk of the mantissa that in turn brings a reduction in the length of the tables. Results are reported for usual elementary func- tions based on exhaustive simulations. A mixed framework including VHDL and Matlab R is used for those simulations.